Current Issues and Prospects of Modern Higher Legal Education in Conditions of the Fight against COVID-19 - Миронець, Оксана Миколаївна; Миронець, О. М.; Миронец, Оксана Николаевна; Myronets, Oksana M.; Данилюк, Іван Васильович; Данилюк, І. В.; Динилюк, Иван Васильевич; Danyliuk, Ivan V.; Дембицька, Наталія Миколаївна; Дембицька, Н. М.; Дембицкая, Наталия Николаевна; Dembytska, Nataliia M.; et al. (IEPDP, 2020)
The purpose of the document is to determine the current problems and the possible directions for the development and improvement of higher legal education in the modern challenges and conditions of the pandemic and post-pandemic of COVID-2019, under the hypothesis that the upcoming emergency is affirmed again. world order. General-scientific and special-legal methods of cognition have been used. Through the use of the dialectical method, the current problems of modern legal education have also been identified, their foundations have been investigated and instructions have been sought to improve legal education and the quality of young lawyers in the educational environment of the pandemic. In conclusion, it is highlighted that the findings found in the research can be useful for higher education teachers who are constantly adapting to the new conditions of professional activity in the field of legal education, in the scene of pandemic and the ordering after the pandemic, with particular emphasis on specialists focused on developing suggestions and improving the quality of legal education in the context of the global challenges imposed by COVID-2019.

Метою документа є визначення поточних проблем і можливих напрямків розвитку та вдосконалення вищої юридичної освіти в сучасних викликах та умовах пандемії та постпандемії COVID-2019 під гіпотезою, що прийдешня надзвичайна ситуація знову затвердиться у світовому порядку. Використовувались загальнонаукові та спеціально-правові методи пізнання. Завдяки використанню діалектичного методу також було виявлено сучасні проблеми сучасної юридичної освіти, досліджено їх основи та розроблені вказівки щодо вдосконалення юридичної освіти та якості молодих юристів в освітньому середовищі пандемії. На закінчення підкреслюється, що висновки, зроблені в дослідженні, можуть бути корисними викладачам закладів вищої освіти, які постійно адаптуються до нових умов професійної діяльності в галузі юридичної освіти, на фоні пандемії та впорядкування після пандемії, особливий акцент робиться на спеціалістів, орієнтованих на розробку пропозицій та поліпшення якості юридичної освіти в контексті глобальних викликів, накладених COVID-2019.

Целью документа является определение текущих проблем и возможных направлений развития и совершенствования высшего юридического образования в современных вызовах и условиях пандемии и постпандемии COVID-2019 под гипотезой, что грядущая чрезвычайная ситуация снова утвердится в мировом порядке. Использовались общенаучные и специально-правовые методы познания. Благодаря использованию диалектического метода также было обнаружено современные проблемы современной юридического образования, исследованы их основы и разработаны указания по совершенствованию юридического образования и качества молодых юристов в образовательной среде пандемии. В заключение подчеркивается, что выводы, сделанные в исследовании, могут быть полезными преподавателям высших учебных заведений, которые постоянно адаптируются к новым условиям профессиональной деятельности в области юридического образования, на фоне пандемии и благоустройства после пандемии, особый акцент делается на специалистов, ориентированных на разработку предложений и улучшения качества юридического образования в контексте глобальных вызовов, спровоцированных COVID-2019.
Myronets O. M. Current Issues and Prospects of Modern Higher Legal Education in Conditions of the Fight against COVID-19 / O. M. Myronets, I. V. Danyliuk, N. M. Dembytska, T. A. Frantsuz-Yakovets, M. O. Dei // Cuestiones Políticas. – V. 37 (65). – IEPDP, 2020. – P. 438-456.
Keywords: pandemic and post pandemic; educational environment; global changes; future lawyers; new world order; пандемія та постпандемія; освітнє середовище; глобальні зміни; майбутні юристи; новий світовий порядок; пандемия и постпандемия; образовательная среда; глобальные изменения; будущие юристы новый; мировой порядок; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::LAW/JURISPRUDENCE